Metformin: A Potential Drug for COVID-19 - Anjali Devi Bettadapura Shankara Rao; Sujatha Puttalingaiah; Ananth B Koushik; Jadeppa Gowda (Indian Journal of Medical Biochemistry)
Metformin is an old drug, of plant origin, primarily used in the treatment of type 2 diabetes. The main mechanism of its action is mediated through adenosine monophosphate (AMP) kinase. Though the main action of metformin is to inhibit hepatic gluconeogenesis, it is also known to increase insulin sensitivity and is used in the treatment of obesity and polycystic ovarian disease. Its varied actions on coronavirus infections, by inhibiting virus entry, preventing cytokine storm, boosting immunity by altering the gut microbiota, and decreasing virulence by inducing autophagy makes it an ideal candidate for treating coronavirus disease-2019 (COVID-19). The only serious side effect of metformin is lactic acidosis, confined to a few patients. The drug is already approved by the US Food and Drug Administration (FDA) and thus repurposing it in COVID-19 patients may be beneficial. Metformin is a drug, approved by FDA for treating diabetes mellitus with very few side effects. It is inexpensive and is known to exhibit anti-COVID-19 actions. It has also proven to be effective in treating PCOS and obesity. Thus, it has all the potential to treat COVID-19.